Jewels and Clothing in the Light of Women’s Wills of the Nobility from Greater Poland (17th Century) - Strojwąs, Klaudia (Respectus Philologicus, 2023)
During the Old Polish period, wills of the nobility were made to transfer property to the beneficiary heirs, revealing evident family relationships. The testators frequently included the record regarding movable possessions, e. g., such as jewels and clothing. The wills of noblewomen show that women had movable assets intended for children, grandchildren, husbands, or siblings. The jewels and clothing mentioned in the records to testified their financial standing. Among the most commonly traded precious items are gold and silver, including chains, pearls, rings, bracelets, and earrings. The wills included various types of outerwear such as coats, cloaks, yupkas, and undergarments such as dresses, skirts and alamodes. Headgear, including caps, hems, and clasps, were also often mentioned in testaments. The testators also had clothing accessories, such as belts, dress sleeves, aprons, cottons, and silver or gilded buttons.